The Distributional Impact of COVID-19 Fiscal Policies on Households, with Emphasis on Da Nang City - World Bank (World Bank, Washington, DC, 2021)
This note will examine the distributional and efficiency issues associated with the fiscal response to the COVID-19 (coronavirus) crisis in Da Nang city and nationally in Vietnam. More specifically, we look at the social assistance (cash transfer) programs. Did these programs efficiently reach people who were the most in need Was the amount of support and the duration of programs sufficient Based on the World Bank COVID-19 monitoring surveys, national-level results indicate that cash transfer programs may have ended prematurely and were not received by the poorest groups or by those who lost their jobs due to pandemic-related factors. Official data also show that the scope of the implementation was smaller than planned, both in the number of new beneficiaries who received access and in terms of the amount spent.